Genome mining and biosynthetic pathways of marine-derived fungal bioactive natural products - Han, Caihua; Song, Anjing; He, Yueying; Yang, Liu; Chen, Litong; Dai, Wei; Wu, Qilin; Yuan, Siwen (Frontiers in Microbiology, 2024)
Marine fungal natural products (MFNPs) are a vital source of pharmaceuticals, primarily synthesized by relevant biosynthetic gene clusters (BGCs). However, many of these BGCs remain silent under standard laboratory culture conditions, delaying the development of novel drugs from MFNPs to some extent. This review highlights recent efforts in genome mining and biosynthetic pathways of bioactive natural products from marine fungi, focusing on methods such as bioinformatics analysis, gene knockout, and heterologous expression to identify relevant BGCs and elucidate the biosynthetic pathways and enzyme functions of MFNPs. The research efforts presented in this review provide essential insights for future gene-guided mining and biosynthetic pathway analysis in MFNPs.